PROFIL PARAMETER KIMIA OSEANOGRAFI PANTAI TIMUR SUMATERA - Fadli, Fani; Samiaji, Joko; Amin, Bintal (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This study was conducted in April-May 2013 in the inner marine waters of the eastern coast of Sumatra and the samples were analyzed in the Chemistry Laboratory of Marine Science Department of Fisheries and Marine Science Faculty of Riau University. This study was aimed to determine the chemical profile of oceanographic parameters in the coastal waters of the east coast of the Sumatra region into two parts, namely the southern and northern parts. Based on the analysis conducted on the chemical oceanographic parameters such as nitrate, nitrite, phosphate, ammonia, dissolved oxygen, and the degree of acidity. Concentration nitrate, nitrite, phosphate, and ammonia has a high concentration values with the approach of sampling stations towards the coast. While the dissolved oxygen and the degree of acidity of the sea towards the higher concentration value. The overall values of water quality parameters were as follow a). In the south section: nitrate 0.0102-0.0890 mg/l, nitrite 0.0675-0.4388 mg/l, phosphate 0.0022-0.0310 mg/l, ammonia 0.0403-0.6602 mg/l, DO 4-7 mg/l, pH 7.48-8.16. b). In the north section: nitrate 0.0025-0.0331 mg/l, nitrite 0.0738-0.1097 mg/l, phosphate 0.0044-0.0177 mg/l, ammonia 0.0333-0.9229 mg/l, DO 5-8 mg/l, pH 7.53-8.15. The physical parameters of the water was a factor in supporting this research.Keywords: East coast of Sumatra, chemical, oceanography